PET CARE KALIMANTAN BARAT DI KOTA PONTIANAK - Nuurkholillah, Busainah; Muazir, Syaiful; Khaliesh, Hamdil (JMARS: Jurnal Mosaik Arsitektur, 2021)
Animals are inseparable from human daily life because life is balanced between humans, animals and the surrounding environment. Pets are domestic animals, for example cats or dogs, kept as friends, treated with love and affection. Some of these animals are kept because of their characteristics or because of their beauty. There is a description in the form of data on animal diseases and animal health which is the main discussion of pet care. In Pontianak City, there are many pet shops or clinics with veterinarians in charge. The location of the pet shops and clinics are scattered and some are joined to or adjacent to shop houses or other public commercial areas. Activities or events are also usually held in public places and are free, not in one fixed place. The design method is to find out something through systematic stages. The design method used is according to J. C. Jones in the book Architectural Design Methods. The stages used are the stages of ideas, information, analysis, synthesis, evaluation, and optimization. The goal to be achieved is to formulate the planning and design of West Kalimantan Pet Care in Pontianak City that can facilitate health facilities, care, care, and activities related to animals, and cafes and retail shops for general visitors.